PENGARUH PENERAPAN MEDIA PEMBELAJARAN QUIZIZZ TERHADAP HASIL BELAJAR GEOGRAFI SISWA KELAS X DI SMAS IT MUTIARA DURI RIAU - mardiah, Hanifah; Nova, Sari (JURNAL BUANA, 2024)
This study aims to determine the effect of applying Quizizz learning media on geography learning outcomes for Class X Students at SMAS IT Mutiara Duri Riau. This type of research is a quantitative research with a type of experimental research (Quasi Experiment Design) with a research design in the form of a pretest posttest control group design. With research subjects namely class X 4 as the experimental class and class X 7 as the control class. The sampling technique used random sampling technique with a total sample of 193 students. The research instrument was a test of 14 objective questions. The results of this study based on the analysis obtained the average posttest score of 87.9 for the experimental class and 73.3 for the control class. In the experimental class, an increase in knowledge or N-Gain of 0.79 was obtained in the high category. Whereas in the control class, an increase in knowledge or N-Gain of 0.54 was obtained in the medium category. The results of the analysis of the two groups used the T test at a significance level ɑ = 0.05 and obtained Tcount = 4.008 and Ttable = 2.024 so that Tcount > Ttable, then H0 is accepted and Hɑ is rejected, meaning that there is an effect of the application of Quizizz learning media on the geography learning outcomes of class X students in Mutiara Duri Riau IT High School. Keywords : Instructional Media. Quizizz. Learning outcomes